2006
DOI: 10.1016/j.clpt.2006.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Low hepatic cytochrome P450 3A activity is a risk for corticosteroid-induced osteonecrosis

Abstract: Low hepatic CYP3A activity may significantly contribute to the risk for steroid-induced ONFH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
24
0
3
Order By: Relevance
“…More recently, low hepatic CYP3A activity was found to be associated with the risk for corticosteroid-induced osteonecrosis (Kaneshiro et al, 2006). Our finding that CYP3A5 polymorphism may influence basal levels of hepatic CYP3A activity and the inductive effects of corticosteroids suggests that absence of CYP3A5*1 alleles may be associated with risk for corticosteroid-induced osteonecrosis.…”
Section: Discussionmentioning
confidence: 57%
“…More recently, low hepatic CYP3A activity was found to be associated with the risk for corticosteroid-induced osteonecrosis (Kaneshiro et al, 2006). Our finding that CYP3A5 polymorphism may influence basal levels of hepatic CYP3A activity and the inductive effects of corticosteroids suggests that absence of CYP3A5*1 alleles may be associated with risk for corticosteroid-induced osteonecrosis.…”
Section: Discussionmentioning
confidence: 57%
“…The bispectral index (BIS) is a processed electroencephalogram (EEG) and a reliable parameter for indicating the depth of anesthesia as well as the levels of sedation used to maintain this depth of anesthesia [2,3]. Although the pharmacokinetics of midazolam has been extensively studied [4][5][6][7][8], little is known about the electroencephalographic effects of higher doses of midazolam used for the induction of general anesthesia relative to those used for sedation [9], and their relationships with plasma and effect site concentrations. We have measured the plasma concentrations of midazolam following bolus administration of two different doses, simulated the effect-site concentrations, and examined the relationships between electroencephalographic parameters, such as BIS, relative beta ratio, and 95% spectral edge frequency (SEF95).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore assumed that genetic variability in metabolizing agents (CYP and UGT family) and drug transporters (ABC family) might be crucial. Some authors showed an association between high risk of steroid induced AVN and low activity of CYP enzymes, especially CYP3A (83,84). These fi ndings were also considered in additional studies.…”
Section: Genetic Polymorphisms Involved In Dna Oxidation Injury In Bomentioning
confidence: 94%
“…These fi ndings were also considered in additional studies. SNPs analysis of the CYP3A4, CYP2D6 and CYP2C19 revealed the association with AVN development (21, [83][84][85]. Different distribution between AVN patients and controls showed 4 SNPs of the CYP2C8 gene and only rs1934951 in this gene was signifi cantly associated with AVN development (86).…”
Section: Genetic Polymorphisms Involved In Dna Oxidation Injury In Bomentioning
confidence: 97%